8-Year Follow-up of a Maternal Education Trial in a Low-Resource Setting - Kakwangire, Paul; Muhoozi, K. M. Grace; Ngari, Moses; Matovu, Nicholas; Westerberg, Cecilie Ane; Iversen, Ole Per; Atukunda, Prudence (Pediatrics, 2024)
OBJECTIVES: Nutrition and stimulation interventions promote early childhood development, but little is known about their long-term benefits in low- and middle-income countries. We conducted a follow-up study of a cluster-randomized maternal education trial performed in children aged 6 to 8 months to assess the sustainability of developmental benefits after 8 years. METHODS: The education intervention lasted 6 months and consisted of nutrition, hygiene, sanitation, and child stimulation aspects. We assessed child processing and cognitive abilities using the Kaufman Assessment Battery for Children Second Edition (KABC-II) and attention and inhibitory control using the Test of Variables of Attention after 8 years. The original trial included 511 mother-child pairs (intervention, n 5 263; control, n 5 248), whereas in the current study, 361 (71%; intervention, n 5 185; control, n 5 176) pairs were available for analyses. RESULTS: The intervention group scored higher than the controls (all P < .001) on all 5 KABC-II subscales and on the KABC-II global score (mean difference: 14; 95% confidence interval, 12–16; P < .001). For all 5 Test of Variables of Attention variables, the intervention group scored higher than the controls on both the visual and auditory tasks (all P < .05). Because the intervention was delivered as a package, a limitation is that we cannot pinpoint the individual contribution of each component (nutrition, hygiene, and stimulation) to the developmental benefits. CONCLUSIONS: The intervention group consistently scored markedly higher on both neuropsychological tests. Thus, even 8 years after the original maternal education intervention, the developmental benefits that we observed at child age of 1, 2, and 3 years, were sustained.
Article